2015
DOI: 10.7747/jfes.2015.31.1.38
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Pine Stumpage Prices Based on Timber Sale Characteristics of the Southern United States

Abstract: The stumpage price changes were calculated and analyzed from the data collected by Timber Mart-South from 1998 to 2007. We analyzed the relationship between pine sawtimber stumpage prices and timber sale characteristics using hedonic pricing method. Quadratic transformation was employed for sale size and contract length. Stumpage prices increased with sale size, contract length, bid sales, and the number of bidders. The presence of above average or excellent grade, market conditions, and logging conditions als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Their findings revealed the impacts of seasonal harvest restrictions, sales volumes, timber assortment, and forest damage on stumpage prices. Kim et al [38], who analyzed the relationship between pine stumpage prices and associated sales characteristics, found that increases in these prices corresponded to increases in the sales volumes, contract length, bid sales, and the number of bidders. Moreover, a positive relationship existed between higher timber grades and better market and logging conditions and stumpage prices.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed the impacts of seasonal harvest restrictions, sales volumes, timber assortment, and forest damage on stumpage prices. Kim et al [38], who analyzed the relationship between pine stumpage prices and associated sales characteristics, found that increases in these prices corresponded to increases in the sales volumes, contract length, bid sales, and the number of bidders. Moreover, a positive relationship existed between higher timber grades and better market and logging conditions and stumpage prices.…”
Section: Introductionmentioning
confidence: 99%